2007
DOI: 10.1016/j.molcel.2007.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Cdc48pNpl4p/Ufd1p Binds and Segregates Membrane-Anchored/Tethered Complexes via a Polyubiquitin Signal Present on the Anchors

Abstract: Cdc48p is an abundant and conserved member of the AAA ATPase family of molecular chaperones. Cdc48p performs ubiquitin-selective functions, which are mediated by numerous ubiquitin binding adaptors, including the Npl4p-Ufd1p complex. Previous studies suggest that Cdc48p-containing complexes carry out many biochemical activities, including ubiquitination, deubiquitination, protein complex segregation, and targeting of ubiquitinated substrates to the proteasome. The molecular mechanisms by which Cdc48p-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 22 publications
4
90
0
Order By: Relevance
“…Western blot analysis of crude extracts from the K. lactis-transformed clones (Fig. 6a) showed a maturation pattern of Mga2 similar to that reported in S. cerevisiae (Shcherbik & Haines, 2007), involving ubiquitination and proteasomal proteolysis.…”
Section: Reciprocal Suppression By Mga2 and Klmga2 In The Deletion Musupporting
confidence: 74%
“…Western blot analysis of crude extracts from the K. lactis-transformed clones (Fig. 6a) showed a maturation pattern of Mga2 similar to that reported in S. cerevisiae (Shcherbik & Haines, 2007), involving ubiquitination and proteasomal proteolysis.…”
Section: Reciprocal Suppression By Mga2 and Klmga2 In The Deletion Musupporting
confidence: 74%
“…Cdc48-Ufd1-Npl4 binds and mobilizes the ubiquitylated and processed p90, separating it from the unprocessed Spt23. These data suggested that Cdc48 acts as a segregase to disassemble protein complexes (Rape et al 2001;Jentsch and Rumpf 2007;Shcherbik and Haines 2007).…”
Section: Cdc48 Atpasementioning
confidence: 92%
“…Most recently, it has been shown that VCP is recruited to stalled proteasomes and relieves their (experimentally induced) impairment (21). It has been suggested that ATP hydrolysisdriven extraction of proteins from larger complexes or membranes, as well as unfolding of proteins by VCP upon recruitment to conjugated (poly)ubiquitin may be the common mechanism underlying the diverse cellular roles of VCP (13,16,22).The energy-dependent, ubiquitin-selective segregase and unfoldase activity of VCP prompted us to investigate whether it has a role in ADIN. The results presented here demonstrate that VCP is an essential cofactor for ADIN and that the ATPase activity of VCP is required when ADIN mediates proteasomal degradation of a challenging substrate such as an adenovirus particle.…”
mentioning
confidence: 99%
“…Most recently, it has been shown that VCP is recruited to stalled proteasomes and relieves their (experimentally induced) impairment (21). It has been suggested that ATP hydrolysisdriven extraction of proteins from larger complexes or membranes, as well as unfolding of proteins by VCP upon recruitment to conjugated (poly)ubiquitin may be the common mechanism underlying the diverse cellular roles of VCP (13,16,22).…”
mentioning
confidence: 99%